2014
DOI: 10.1002/app.40646
|View full text |Cite
|
Sign up to set email alerts
|

New filtrate loss controller based on poly(methyl methacrylate‐co‐vinyl acetate)

Abstract: The drilling of petroleum wells requires the use of suitable drilling fluids to ensure efficient operation without causing rock damage. Specific polymers have been used to control infiltration during drilling, to reduce operational problems. In this study, spherical microparticles of poly(methyl methacrylate‐co‐vinyl acetate) were synthesized (by suspension polymerization), characterized, and evaluated in terms of their performance in controlling filtrate loss of aqueous fluids. A filter press test with cerami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Compared to the high costs of the operational chain, the cost of drilling fluids is relatively small, representing about 15 to 18%. However, the majority of problems encountered during drilling operations are, to lesser or greater extent, associated with a deficiency in the fluid's properties …”
Section: Introductionmentioning
confidence: 99%
“…Compared to the high costs of the operational chain, the cost of drilling fluids is relatively small, representing about 15 to 18%. However, the majority of problems encountered during drilling operations are, to lesser or greater extent, associated with a deficiency in the fluid's properties …”
Section: Introductionmentioning
confidence: 99%
“…Amphiphilic polymers have widespread applications. In the petroleum industry, they are used in drilling fluids and for demulsification of water‐in‐oil emulsions, inhibition of wax deposition, stabilization of asphaltenes in crude oil, flocculation of asphaltenes, inhibition of naphthenate deposition, enhanced oil recovery, and water treatment . In drilling, hydrophobically modified starches can be used to control filtrate from emulsified fluids .…”
Section: Introductionmentioning
confidence: 99%
“…The backbone was humic acid, and the lateral terpolymer chains contained the monomers of sodium 2‐acrylamido‐2‐methylpropane sulfonate, N,N‐dimethyl acrylamide, and acrylic acid . A new spherical microparticles of poly(methyl methacrylate‐co‐vinyl acetate) was synthesized by Nunes et al . It was observed that the performance of the material is related to the rubbery characteristic which forms the desirable filter cake to block the entrance of fluid into the formation.…”
Section: Introductionmentioning
confidence: 99%